KONSEP PENDIDIKAN ANAK USIA DINI DALAM ISLAM MENURUT IBNU QOYYIM AL-JAUZIYYAH - Nur Mashani; Eka Saptaning Pratiwi (LPPM STAI Muhammadiyah Probolinggo, 2022)
This study aims to find out an in-depth picture of the Concept of Islamic Early Childhood Education, especially according to Ibnu Qoyyim Al Jauziyyah. This study used the literature study method with Tuhfatul Maudud Bi Ahkamil book as the primary sources and written data, books, the results of studies and research, Ibnu Qayyim Al- Jauziyyah’s other work which talked about education, particularly about early childhood education as the secondary sources. The results of the study showed that the concept of early childhood education according to Ibnu Qayyim Al- Jauziyyah was an early childhood education concept applied to children aged 0-6 years old. Where this characteristic of education according to Ibnu Qayyim Al-Jauziyyah is the beginning for the further development of children's education. The age stage of 0-2 years as the beginning of the child's life so that the concept of education focuses on when the child is just born, the call to prayer to circumcision. Meanwhile, the age stage of 3-6 years of educational responsibility focuses on faith, moral, social, and intellectual education.Keywords : Ibnu Qoyyim Al-Jauziyyah, Early Childhood Education, Islamic Early Childhood Education, Islamic Studies.